2017
DOI: 10.3390/f8050156
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Shade, Fertilizer, and Pruning on Eastern Hemlock Trees and Hemlock Woolly Adelgid

Abstract: Hemlock woolly adelgid (HWA), Adelges tsugae Annand, an invasive insect native to the Pacific Northwest and Asia, is responsible for widespread health decline and mortality of native hemlocks (Tsuga spp.) in the eastern United States. Shading and fertilizer has been found to affect the survival and health of both HWA and hemlocks. These abiotic factors have been studied separately but not in combination. In this three year study, eastern hemlock trees (1-2 m tall) were treated with pruning, fertilizer, and sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Higher HWA densities in low light conditions were found by Brantley [34], Sussky and Elkinton [69], Mayfield and Jetton [70], and Hickin and Preisser [71]. Mech [33] reported increased mortality of summer aestivating sistens with increases in temperature, particularly above 30 • C. McAvoy [35] reported that HWAs developing under shade had twice the survival rate compared to HWAs growing in full sun. Summer aestivating morality would be lower in the northern latitudes due to lower summer temperatures.…”
Section: Discussionmentioning
confidence: 85%
“…Higher HWA densities in low light conditions were found by Brantley [34], Sussky and Elkinton [69], Mayfield and Jetton [70], and Hickin and Preisser [71]. Mech [33] reported increased mortality of summer aestivating sistens with increases in temperature, particularly above 30 • C. McAvoy [35] reported that HWAs developing under shade had twice the survival rate compared to HWAs growing in full sun. Summer aestivating morality would be lower in the northern latitudes due to lower summer temperatures.…”
Section: Discussionmentioning
confidence: 85%
“…Negative phototaxis has also been observed in other groups of insects including haematophagous bugs (Lazzari et al, 1998) and stored grain beetles (Kim et al, 2013). As noted by McAvoy et al (2017), hemlocks are very shade-tolerant and frequently grow in the forest understory, so if A. tsugae is adapted to cool, shaded environments, sunlight avoidance may help them locate cooler settling sites. This hypothesis is consistent with experiments by Mech et al (2018), who documented an increase in the mortality of aestivating A. tsugae sistens nymphs with increases in temperature, a relationship that strengthened with increasing duration of exposure, particularly above 30 ∘ C. Sussky and Elkinton (2015) also reported high levels of aestivating sistens mortality associated with elevated temperatures.…”
Section: Shade Cloth Experimentsmentioning
confidence: 84%
“…(3) predation risk on pests associated with certain predators and their abundance at different edges (including the "natural enemies hypothesis" prediction that higher plant diversity systems support more insect predators that more effectively control herbivore populations [29,33]), and (4) pest ecophysiological and life-history traits that are associated with ecological features and physical positions (i.e., forest layers) at forest edges [34].…”
Section: Discussionmentioning
confidence: 99%